Long‐term efficacy and safety of adjunctive perampanel in patients from the Asia‐Pacific region with refractory focal‐onset seizures in Study 335 open‐label extension - Takuji Nishida; Sang Kun Lee; Yushi Inoue; Kazunori Saeki; Kohei Ishikawa; Manoj Malhotra; Anna Patten; Sunao Kaneko (Epilepsia Open, 2024)
Abstract Objective To evaluate the long‐term efficacy, safety, and tolerability of adjunctive perampanel for the treatment of patients with refractory focal‐onset seizures (FOS), with or without focal to bilateral tonic–clonic seizures (FBTCS), from the Asia‐Pacific region. Methods Study 335 (NCT01618695) was a randomized, double‐blind, placebo‐controlled, Phase III study. Patients aged ≥12 years with refractory FOS who completed the Core Study could enter an open‐label extension (OLEx) Phase (6‐week Conversion and ≥46‐week Maintenance Period). Endpoints included median percent reduction in seizure frequency per 28 days, 50% responder and seizure‐freedom rates, and treatment‐emergent adverse events (TEAEs). Results The Intent‐to‐Treat Analysis Set included 704 patients (529 received perampanel and 175 received placebo during the Core Study; all patients received perampanel during OLEx). The median percent reduction in seizure frequency and 50% responder rates in patients who received perampanel during the Core Study were maintained throughout the OLEx Phase (Week 64–75: 55.9% and 54.3%, respectively). Seizure freedom for ≥12 consecutive months at any time during perampanel treatment was achieved by 4.1% of patients with FOS and 14.2% of patients with FBTCS. Among patients treated with perampanel 4 mg/day (n = 83), median reduction in seizure frequency was lower in those who received concomitant enzyme‐inducing anti‐seizure medications (EIASMs) than those who received non‐EIASMs. The most common TEAE was dizziness (n = 318; 46.8%); 141 (20.8%) patients had TEAEs that led to study/drug withdrawal. Significance Overall, long‐term seizure control was achieved with adjunctive perampanel in patients with refractory FOS, with or without FBTCS, in an Asia‐Pacific population.